Common Complementary Feeding Practices Among Under-Five Children: The Case of Zambia - Raider Habulembe Mugode; Musonda Mofu; Oliver Mweemba (International Journal of Nutrition, 2019)
Introduction In the past several decades, Zambia has suffered high levels of under nutrition particularly stunting among children below 5 years of age. Although appropriate complementary feeding practices are reported to reduce child deaths by 6%, they have not received the adequate attention from programme officers and caregivers in terms of implementation. Objectives The objective was to investigate issues surrounding the common complementary feeding practices practised by caregivers of children below five years in health facilities and areas where high rates of malnutrition admission come from. Design A cross sectional research using both qualitative and quantitative methods. The study used mostly proportions based mostly on global indicators on complementary feeding. Qualitative data was also analysed according to themes of global complementary feeding indicators Setting The study was conducted in five hospitals, namely Arthur Davison, Solwezi Central, Kabwe and Livingstone General, and University Teaching Hospital. Subjects The target populations were mothers whose children were admitted for malnutrition and those with children 0-59 months living in communities with the highest number of malnourished cases admitted to selected hospitals Results About45.2% (190) of caregivers introduced liquids before six months of age and 7.6% (32) after 6 months attributing child thirst, medication and advice from health worker as the main reasons. Slightly above half (54.2% of 224) of mothers/caregivers used cups to feed their babies. The use of feeding bottles was still common (8.2% of 34). Responsibility to feed the child is mostly left to the mother (86.4%, 362). In addition, children were being feed about 2.67 (SD 0-72) per day. Conclusions Child feeding practices were still poor. This contributes to poor child growth and health. More interventions should be planned to improve child care behaviour.
Keywords: caregivers